Upaya Peningkatan Kualitas TPQ Desa Bitingan Melalui Pendampingan Pembuatan Perangkat Pembelajaran Berbasis Community Based Participatory Research - Febriyanti, Fitri; Sri Devi Rahayu; Affinda Aulia; Jannatu Nur Fitriani; Nor Santi; Dewi Mabruroh; Lathifah Arifana (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Bitingan Village has three TPQs in each hamlet, namely Dukuh Ledok, Krajan, and Ngeso with various challenges and obstacles they face. According to the number of pupils and teachers, the three TPQs have a strong future. This study intends to explain actions taken in TPQ Bitingan Village to raise the standard of non-formal education by assisting in the development of instructional materials based on community-based participatory research (CBPR). Laying the groundwork, planning the research, gathering and analyzing the data, and taking appropriate action are all parts of the CBPR method. The TPQ Bitingan Village received assistance in creating instructional materials, such as a curriculum, manual, and achievement book, in addition to assisting in strengthening their organizational structure. Due to their shared enthusiasm and teamwork, the Bitingan Village TPQ teaching staff can provide any assistance successfully. The issues that exist in each TPQ still haven't been completely fixed as a result of our assistance. The actions taken can improve the abilities of the teaching staff and develop a more professional organizational management environment.